Coupled Cluster Wave Functions for Ground State Wave Function for Many Physical System (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and found coupled cluster wave functions as important functions  for a projection quantum Monte Carlo algorithm within the configuration interaction  scheme. The ground state wave function of a configuration interaction Hamiltonian  is filtered out by propagating the amplitudes of an initial arbitrary wave function via  a random walk in the many body Hilbert space spanned by a basis of Slater  determinants. The coupled cluster wave functions are used to guide this random  walk via importance sampling in order to circumvent the sign problem. This  approach has provided upper bounds to the ground state energy whose tightness  can be systematically improved by including higher order excitations in the coupled  cluster wave function. We have applied three dimensional homogenous electron gas  in momentum space. The electron gas was studied for large single particle basis  sizes. We found that coupled cluster wave functions are very accurate and good  approximation for ground state wave function for many physical systems. The  obtained results were in good agreement with previously obtained results.